ANALYSIS OF DEVELOPMENT TRENDS AND EXPORT STRUCTURE OF UZBEKISTAN'S ICT SERVICES MARKET - Shermatov , Sherzod (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
Issues regarding the development trends of Uzbekistan's ICT services market and the analysis of export structure are extensively covered. It provides an in-depth analysis of the theoretical foundations of service export, its impact on economic growth, and development trends in the digital economy. The study also examines the development of the ICT services market in Uzbekistan, the structure of exports, and their impact on economic growth. The current state of ICT service exports was assessed, and factors hindering development were identified. Practical proposals have also been developed to increase export potential in the fields of IT services, startups, human resources, outsourcing, GovTech, and SaaS.